Hukum Khitbah, Mahar Bagi Wanita yang Dicerai dan Muth’ah Tholaq - Miftakhul Anwar (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2021)
This article discusses the interpretation of Q.S Al-Baqoroh verses 235-237 which discusses the law of khitbah, dowry for divorced women and muth'atut tholaq from the perspective of Imam Fakhruddin Ar-rozi's interpretation of mafatihul ghoyb. In this article explained the law of each of the laws of khitbah, dowry for divorced women and muth'atut tholaq. This commentary study includes a thematic interpretation model that discusses a certain maudhu/tem in the Qur'an. In this study the data obtained through a literature review and processed using a descriptive-comparative method. This study aims to provide an understanding and reduce disputes between two families experiencing problems of khitbah and divorce..